Green Decoupling: Geoeconomic Interdependence, Environmental Regulation, and the Reconfiguration of Global Supply Chains after 2020 - Chen, Ze (Journal of Neonatal Surgery, 2025)
This meta-analysis examines the phenomenon of green decoupling in global supply chains following 2020, synthesizing evidence from 47 empirical studies. We analyze how environmental regulations and geoeconomic tensions have jointly influenced supply chain reconfiguration across manufacturing sectors. Our systematic review reveals three primary patterns: (1) accelerated nearshoring in carbon-intensive industries under stringent environmental policies, (2) diversification strategies balancing cost efficiency with regulatory compliance, and (3) technology-driven optimization enabling simultaneous emissions reduction and supply chain resilience. Statistical analysis of 156 firm-level restructuring decisions demonstrates that environmental regulation stringency (β = 0.42, p < 0.001) and geopolitical risk exposure (β = 0.38, p < 0.001) independently predict supply chain reorganization. However, their interaction effect (β = 0.15, p < 0.05) suggests synergistic dynamics. Results indicate that green decoupling is most pronounced in automotive, electronics, and chemical sectors, with estimated emission reductions of 18-34% alongside supply chain regionalization. These findings contribute to understanding how firms navigate the dual pressures of sustainability imperatives and geopolitical fragmentation in post-pandemic global economy